Tribe Teruliini: new genera and new species of Neotropical leafhoppers with a revised key to genera and species, new records and notes on distribution and taxonomy (Hemiptera: Cicadellidae: Coelidiinae) - Nielson, M. W. (Zootaxa, 2011)
Two new genera, Freytagolidia, type-species Freytagolidia ligula sp. nov. and Neodocalidia, type-species Neodocalidia connectiva sp. nov., from Colombia are described and illustrated. Nineteen additional new species are described and illustrated in the following genera: Baluba sharkeyi sp. nov. (Colombia), Bolidiana robusta sp. nov. (Colombia), B. trisetacea sp. nov. (French Guiana), B. elongata sp. nov. (Colombia), Harasupia lyrata sp. nov. (Mexico), Hastalidia acinaca sp. nov. (Peru), Jalorpa constricta sp. nov. (Colombia), Licontinia minutasetacea sp. nov. (Colombia), L. recurvata sp. nov. (Panama), Panolidia torquersi sp. nov. (Colombia), P. minuta sp. nov. (Colombia), Sapingia calcaris sp. nov. (Colombia), Stalolidia flangella sp. nov. (Colombia), S. semiovata sp. nov. (Colombia), S. setacea sp. nov. (Colombia), S. ecuadorensis sp. nov. (Ecuador), S. lyrica sp. nov. (Bolivia), S. clava sp. nov. (Brazil) and S. bulbata sp. nov. (Peru). Taxonomy and distribution of genera, revised key to species and details on new records are provided. A revised key to all known genera is also included. Colombia is a new record for Baluba, Jalorpa, Panolidia, Sapingia and Stalolidia; Panama for Licontinia; Peru for Hastalidia and Ecuador for Stalolidia. The type-species name, Coelidia marginata Stål, for Harasupia Nielson, 1979 was incorrectly cited as Harasupia marginata (Stål) and is corrected herein.